Agent-based modelling of water price negotiation for domestic water management in deurbanisation society of Kanazawa City, Japan. (1st January 2013) - Ma, Yan; Shen, Zhenjiang; Kawakami, Mitsuhiko; Suzuki, Katsunori; Long, Ying
To coordinate urban development with domestic water demand, this paper introduced an agent-based model of household water consumption simulation (HWCSim) to simulate the volume of household water consumption regulated by government total amount control. An important water price negotiation module is embedded in HWCSim model to determine the charge price of water resource during government total amount control. The simulation result shows that the volume of household water consumption could be basically regulated through government adjustment of water price according to the control threshold of regional water supply capacity.